Development of a mobile expert system for the diagnosis on motorcycle damage using forward chaining algorithm - Rizqi Fitri Naryanto; Mera Kartika Delimayanti; Kriswanto Kriswanto; Ari Dwi Nur Indriawan Musyono; Imam Sukoco; Mohamad Naufal Aditya (Institute of Advanced Engineering and Science, 2022)
Indonesia is an ASEAN country with the most motorcycle users, where one-third of its population own motorcycles. The automatic motorcycle is the most widely used type due to its agility and fuel-efficient abilities. Sudden motorcycle damage could hamper the users' activities. However, most of these users do not know the reason for the damage. This paper presents the development of expert system for diagnosing the damage of motorcycle using forward chaining method. This system was implemented in mobile application. Through a mobile application, a solution for these users can be obtained. This application immediately discovers the damaged location and repair process. Furthermore, it acts as the first solution before motorcycle repair is carried out in a shop. In this study, the forward chaining method was implemented. It is based on a pattern-matching algorithm whose primary objective is to match facts (input data) with appropriate rules from the rule base. Various test results showed that the diagnostic application used for automatic motorcycle damages 100% worked.